Actividad parasitaria de spalangia endius walker y muscidifurax raptorellus kogan y legner (hymenoptera: pteromalidae) sobre musca domestica L. - Inciso, Edgar; Iannacone, José (Instituto de Ecología, A.C., 2008)
The employment of parasitoid microwasps of pupae state of Musca domestica L. emerge as an important alternative of biological control which could result effective. In the current research, a comparative study of the parasitical activity of Spalangia endius Walker and Muscidifurax raptorellus Kogan & Legner over pupae of M. domestica in laboratory bioassays was performed, under controlled condition of temperature (according to each assay), relative humidity (75 ± 3 %) and darkness. The temperature (15°C, 20°C, 25 °C and 28 °C) influence on biological cycle and longevity of both parasitoids was analyzed, being 25 °C, the optimal temperature of breeding. At this temperature, the biological cycle duration of S. endius (22.6 days) was greater in comparison to M. raptorellus (14.8 days). The biological cycle length was in inverse relation with temperature for both species. The longevity in both species was statistically the same for both species (20.7 days for S. endius and 18.6 days for M. raptorellus). The oviposition capacity at 25 °C with 20 pupae as constant host population was analyzed, obtaining for S. endius, 15 days of oviposition with 175 parasitized pupae in total; by contrast M. raptorellus parasitized 140 pupae in 16 days. The highest oviposition for both species was the third day. The phenological state of maturation over susceptible pupae of M. domestica to be parasitized was determined, at 25 °C in groups of 50 pupae of 1, 2, 3 and 4 days old. The pupae of two days of maturation were the most parasitized obtaining 66.4 % of effective parasitism for S. endius and 60.2 % for M. raptorellus Moreover, the optimal number of pupae of housefly to be expose to both parasitoid species was determined; of the nine relations of parasitism performed (1:5 to 1:50), the optimal number of pupae was the relation 1:10. Finally, in laboratory conditions, the microwasp S. endius resulted being the parasitoid more effective in comparison to M. raptorellus and could be considerate an efficient biological control of pupae of M. domestica.